Qualitative analysis of monomers released from 3D printable MED610 polymer and their effect on cells - Youssef Adelina Stephanie; Ferenc Tóth; Csaba Hegedűs; Melinda Szalóki (Hungarian Dental Association, 2021)
Thanks to the dynamically evolving 3D printing technology, the use of 3D printing is becoming more and more widely used besides the industrial areas by medical sciences as well. The most commonly used materials in dentistry are poly- mers, and their biocompatibility is a key question when used in oral environments. Our aim was to identify the components released from the biocompatible MED610 (Stratasys, USA) polymer samples and to monitor their effects on bonederived cells. During the research, the biocompatibility of the polymer was investigated, and its effect on osteosarcoma (SAOS-2) cell proliferation was observed. In the series of experiments objects of various sizes, shapes and surface area sizes were printed of MED610 polymer with Objet 30 Orthojet (Stratasys, USA) printer and the objects were surface treated according to the manufacturer's instructions. Printed samples were exposed directly or indirectly to Sarcoma Osteogenic-2 (SAOS-2) cells during the experiments. The dissolution assay of MED610 was performed for 7 days using 11 samples in methanol and analyzed by gas chromatography - mass spectrometry coupled method (GC-MS). The components were identified by MS search based on MS spectra. As a result, several components were identified, three in relatively large amounts. These were isobornyl acrylate, hydroxycyclohexyl-phenyl-ketone and caprolactone. The effect of the different dimensions of the MED610 polymer on the proliferation of SAOS-2 cells was studied by alamarBlue assay (Thermo Fisher Scientific, USA). Based on the results of cell viability assays, MED610 significantly decreases SAOS-2 cell proliferation in parallel with surface increment, which is enhanced by direct exposure to the substance. The effect we are observing is probably caused by the toxic substances liberated from MED610. In case of a bigger surface area, the substances are released more rapidly from MED610 and thus are present in higher concentrations in the cellular environment.